A comprehensive review of performance enhancement of hybrid rice husk polymer resin biocomposite - Haruna, Badamasi; Abdullahi, Ibrahim; Abdullahi, Umma (Journal of Umm Al-Qura University for Engineering and Architecture, 2025)
This work studies the development, characterization, and performance assessment of biocomposites made from hybrid rice husk polymer resin, incorporating findings from numerous researches. The growing call for sustainable and high-performance composite materials has led to wide research into hybrid biocomposites that integrate rice husk (RH) as essential reinforcement. The blend of RH with natural fibers such as kenaf, aloe vera, banana, ramie, and Borassus flabellifer and synthetic reinforcements like glass fiber, carbon fiber, and nanocellulose has been studied to improve thermal, mechanical, and physical properties. Different polymer resins, including epoxy, polyester, and polyethylene, have been used as matrix materials, each conveying unique impacts on the composite’s performance. The choice of composite fabrication methods such as compression molding and hand lay-up, resin infusion are vital for attaining structural integrity and optimal properties. Performance evaluation methods, including thermal analysis (TGA and DSC), tensile testing, and biodegradation studies, have revealed that hybridization significantly enhances tensile strength, impact resistance, thermal stability, and environmental durability. Nonetheless, challenges such as moisture absorption, interfacial bonding, and long-term degradation continue to raise critical concerns. This review recognizes existing gaps in research, mostly the limited exploration of long-term durability, fatigue behavior, and industrial scalability. Future researches should focus on enhancing fiber-matrix adhesion, developing innovative surface treatments, and adopting sustainable processing techniques to improve the practical application of hybrid rice husk-based biocomposites. Lastly, this study outlines the potential of hybrid rice husk polymer resin biocomposites as a viable and sustainable substitute for structural and engineering applications.